2009
DOI: 10.1111/j.1445-5994.2008.01786.x
|View full text |Cite
|
Sign up to set email alerts
|

Prior diabetes mellitus is associated with increased morbidity in cystic fibrosis patients undergoing bilateral lung transplantation: an ‘orphan’ area? A retrospective case–control study

Abstract: Almost all cystic fibrosis patients develop hyperglycaemia after lung transplantation, but patients with prior diabetes have more complication-related admissions to hospital and a higher mortality rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 23 publications
(45 reference statements)
1
36
0
Order By: Relevance
“…Few studies have addressed the potential impact of DM on post-transplantation survival in CF. One small study from Sydney found hyperglycaemia postoperatively in almost all CF patients, but more pronounced in DM [6]. In that study, patients with a diagnosis of DM prior to LTx had more hospital admissions, complications and a higher mortality rate after LTx.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Few studies have addressed the potential impact of DM on post-transplantation survival in CF. One small study from Sydney found hyperglycaemia postoperatively in almost all CF patients, but more pronounced in DM [6]. In that study, patients with a diagnosis of DM prior to LTx had more hospital admissions, complications and a higher mortality rate after LTx.…”
Section: Discussionmentioning
confidence: 94%
“…DM is associated with more severe disease and poor health [9], but it is unclear whether it affects survival of CF patients following successful LTx [10,11]. Among two recent studies addressing a potential impact of DM on outcome after LTx, one reported a worse outcome for CF recipients with a preoperative diagnosis of DM, whereas the other found no significant difference between recipients with DM and those without DM [6,10].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Further, the mechanisms by which DM increases morbidity and mortality have not been well evaluated. A small study showed that patients with cystic fibrosis (CF) with pretransplant DM who underwent LTx had more hospital re-admissions with infection and likely rejection as well as a higher mortality than patients without DM (13). Another retrospective study showed an association between new onset DM after LTx and acute rejection (14), although this may reflect DM diagnosis in the setting of high dose glucocorticoid therapy used for rejection.…”
Section: Introductionmentioning
confidence: 98%
“…11 Post-transplant diabetes is common in CF, but the impact of pre-transplant CFRD upon graft survival is not well defined. 12 The mechanisms linking CFRD with inflammation and pulmonary decline have yet to be resolved. In vitro studies identifying increased growth of Staphylococcus aureus and Pseudomonas aeruginosa with increasing airway surface liquid glucose concentration 13,14 support a direct role for hyperglycemia promoting pathogens.…”
Section: Introductionmentioning
confidence: 99%